2020
DOI: 10.3389/fimmu.2020.00539
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated CD4+ T Cells and microRNAs in Myocarditis

Abstract: Myocarditis is a polymorphic disease complicated with indeterminate etiology and pathogenesis, and represents one of the most challenging clinical problems lacking specific diagnosis and effective therapy. It is caused by a complex interplay of environmental and genetic factors, and causal links between dysregulated microribonucleic acids (miRNAs) and myocarditis have also been supported by recent epigenetic researches. Both dysregulated CD4+ T cells and miRNAs play critical roles in the pathogenesis of myocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 165 publications
0
33
0
2
Order By: Relevance
“…CD4 + T cells are key pathogenic players underlying the development and progression of myocarditis, and the effector subsets promote autoimmune responses [ 22 ]. Therefore, we next assessed the CD4 + T-cell function of rBCG-MyHCα-immunized mice.…”
Section: Resultsmentioning
confidence: 99%
“…CD4 + T cells are key pathogenic players underlying the development and progression of myocarditis, and the effector subsets promote autoimmune responses [ 22 ]. Therefore, we next assessed the CD4 + T-cell function of rBCG-MyHCα-immunized mice.…”
Section: Resultsmentioning
confidence: 99%
“…132 These are classified into myomiRs, and those related to cardiotropic virus infections, immune status, and fibrosis. 132 Since miRNAs can epigenetically regulate cardiac functions, their ablations can lead to developmental defects in the cardiovascular system and also alter immune functions. 133,134 For example, deficiency of miR155 led to attenuated CVB3 myocarditis occurring in association with reduced CD45 + infiltrations in hearts with an immune response skewed toward Th2 and M2 polarizations, suggesting that miR155 has a prominent role in disease induction with CVB3.…”
Section: Other Knockout Modelsmentioning
confidence: 99%
“…It has been recently appreciated that miRNAs have a role in the development of myocarditis based on the detection of dysregulated intracellular miRNAs in heart biopsies in patients with myocarditis and DCM 132 . These are classified into myomiRs, and those related to cardiotropic virus infections, immune status, and fibrosis 132 .…”
Section: Cvb3‐induced Myocarditis In the Mousementioning
confidence: 99%
See 1 more Smart Citation
“…Infection with the novel pathogen severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may trigger myocarditis both directly and indirectly ( 14 , 21 ). Several studies have suggested that the immune response triggered by the virus is the major cause of cardiomyocyte injury, rather than direct virus-mediated cytotoxicity ( 15 , 22 ). In a recent series of hospitalized coronavirus disease 2019 (COVID-19) cases caused by SARS-CoV-2 infection, acute cardiac injury with serum troponin elevation occurred in 7% to 27% of patients, and elevated troponin levels were associated with increased mortality in patients with COVID-19 ( 23 25 ).…”
Section: Triggers Of Myocarditismentioning
confidence: 99%